Antimicrobial Efficacy of a Historical High-Frequency Plasma Apparatus in Comparison With 2 Modern, Cold Atmospheric Pressure Plasma Devices. (August 2015) - Daeschlein, Georg; Napp, Matthias; von Podewils, Sebastian; Scholz, Sebastian; Arnold, Andreas; Emmert, Steffen; Haase, Hermann; Napp, Judith; Spitzmueller, Romy; Gümbel, Denis; Jünger, Michael
Background . Today, highly sophisticated devices deliver cold atmospheric pressure plasma (CAPP) with a multitude of bioactive properties, opening the window to a new medical field: plasma medicine. Different techniques to create the optimal plasma device for different medical indications are currently being explored. However, even a 100 years ago, CAPP was briefly used in the related form of high-frequency therapy. The objective of our study was to compare historic with modern techniques regarding antimicrobial efficacy. Methods . First, 26 different clinical isolates of relevant wound pathogens were treated in vitro with a historic violet wand (VW) and 2 modern plasma sources (kINPen 09 and dielectric barrier discharge [DBD]) and the obtained inhibition areas (IAs) were compared. Second, a biofilm model was used to compare biofilm inactivation by VW, DBD, ethanol, and polyhexanide treatment. Results . DBD with the largest electrode produced the largest IAs. VW showed results similar to 2 different modes of the kINPen 09. IAs of VW were enlargeable by attaching a larger electrode. Against biofilms, VW was less effective than DBD but more effective than ethanol 70% and polyhexanide. Conclusion . The proven antimicrobial efficacy of VW may encourage the development of new, potent plasma devices based on the very simple and inexpensive technique of the historic high-frequency apparatus.